Relationship between Anxiety and School Violence: Econometric Analysis in Secondary School Students - Murillo , Hernán Javier Guzmán; Ortega, José Marcelo Torres; Niebles, William (Journal of Ecohumanism, 2024)
This study analyzes the relationship between state anxiety levels (ERS) and school violence (ERAVE) among secondary school students using a simple linear econometric model. A quantitative design with correlational and explanatory analysis was applied. The sample included secondary-level students, and the ERS and ERAVE scores were used to examine the correlation and the predictive effect of anxiety on school violence. Results indicated a weak positive correlation between both variables (r = 0.1388) and a regression coefficient of 0.16557, suggesting that increased anxiety is associated with a slight increase in school violence. The model was statistically significant (p = 0.0499) and passed tests for linearity, functional specification, and homoscedasticity. However, the low determination coefficient (R² = 1.9%) indicates that anxiety explains only a small proportion of the variance in school violence, highlighting the need to explore other contributing factors. These findings emphasize the importance of psychoeducational interventions for emotional management and the prevention of violent behavior in school settings.